The differentiated equation appears as db = dl = [tex]-\frac{h}{b}[/tex] dh = [tex]-\frac{h}{b}[/tex]x
By applying Pythagoras Theorem,
[tex]\frac{h^2}{4}[/tex] + [tex]\frac{b^2}{4}[/tex] = [tex]a^{2}[/tex]
⇒ [tex]h^{2}[/tex] + [tex]b^{2}[/tex] = 4[tex]a^{2}[/tex]
Then differentiating the equation, we have
2hdh + 2bdb = 0..... (da = 0)
So db = dl = [tex]-\frac{h}{b}[/tex] dh = [tex]-\frac{h}{b}[/tex]x
The Pythagorean Theorem states that the squares on the hypotenuse (the side across from the right angle) of a right triangle, or, in familiar algebraic notation, a2 + b2, are equal to the squares on the legs.
Book I, Proposition 47, that is also known as I 47 or Euclid I 47, was mentioned and demonstrated for the first time by Euclid. Among all the Pythagorean proposition proofs, this one is arguably the most well-known.
To know more about Pythagoras theorem visit:
https://brainly.com/question/343682
#SPJ4